Alien plants in field margins and fields of southwestern Poland - Dajdok, Zygmunt; Wuczyński, Andrzej (Biodiversity: Research and Conservation, 2008)
Field margins are generally considered as important semi-natural habitats in intensive agricultural landscapes. Also, they are areas of regular and extensive disturbance by anthropogenic factors. As such, field margins are likely to be dominated by alien plants, including invasive species. This paper examines the relative abundance of alien and native plant species occurring in seventy field margins and adjacent crop fields in SW Poland, as well as the mutual relationship between different groups of alien species. Anthropophytes constituted 22.5% of the 435 vascular plants recorded in 1319 phytosociological relevés. They were twice as abudant in crop fields than in field margins. Most of the alien species identified were archaeophytes, the percentage of neophytes was much lower, and ergasiophygophytes were found sporadically. Archaeophytes were substantially more frequent in the peripheral (adjacent to crop fields) zones of the margins than in their interior. This suggests the direction in which these species disperse - from cultivated fields to field margins. Neophytes were more evenly distributed throughout the various zones. Only six alien species (all of them archaeophytes) recorded in the relevés are considered endangered in the studied region. The habitats examined were also only slightly colonized by the most invasive alien species. This suggests that plant communities of the field margins are still resistant to invasion. Results indicate, that field margins play only a minor role in the distribution and dispersion of alien species and are far more important reservoir of native plants. Although low number of plant species of special conservation value was located in field margins, they should deserve special protection in intensive agro-ecosystems because they harbour a suite of plants not found in other farmland habitats.